The effectiveness of board games to promote student attention and enjoyment in English subject / Umairah Zulkefli and Amirah Mohd Juned - Zulkefli, Umairah; Mohd Juned, Amirah (Academy of Language Studies, 2023)
This project aims to observe the effectiveness of creating an educational board game and the presence of fun environment in improving children's English skills in relation to the following criteria: spelling, vocabulary, and creating sentences. It covers the absence of an educational and fun source for children during their English learning session. The subjects were the teachers, parents, or guardians of children aged five to nine, and 21 students with 1 teacher from a kindergarten. The results and discussion demonstrate that the subjects leaned towards the idea of creating a fun way to enhance children's English skills, and conclude that it helps the students to understand better and make them be interested in learning. Further discussion reveals that children felt motivated to learn and were able to improve their English skills by playing the educational board game. It was evident that children learn better when an educational board game is applied during a learning session, as it creates a fun environment for them. Hence, this project can be used as one of the learning materials for teachers, parents or guardians in order to improve children’s English skills through fun learning.